Experience-Dependent Changes in Myelin Basic Protein Expression in Adult Visual and Somatosensory Cortex - Murphy, Kathryn M.; Mancini, Steven J.; Clayworth, Katherine V.; Arbabi, Keon; Beshara, Simon (Frontiers in Cellular Neuroscience, 2020)
An experience-driven increase in oligodendrocytes and myelin in somatosensory cortex (S1) has emerged as a new marker of adult cortical plasticity. That finding contrasts with the view that myelin is a structural brake on plasticity, and that contributes to ending the critical period (CP) in visual cortex (V1). Despite the evidence that myelin-derived signalling acts to end CP in V1, there is no information about myelin changes during adult plasticity in V1. To address this, we quantified the effect of 3 manipulations that drive adult plasticity (monocular deprivation (MD), fluoxetine treatment or the combination of MD and fluoxetine) on the expression of myelin basic protein (MBP) in adult rat V1. In tandem, we validated that environmental enrichment (EE) increased cortical myelin by measuring MBP in adult S1. For comparison with the MBP measurements, 3 plasticity markers were also quantified, the spine markers drebrin E and drebrin A, and a plasticity maintenance marker Ube3A. First, we confirmed that EE increased MBP in S1. Next, that expression of the plasticity markers was affected in S1 by EE and in V1 by the visual manipulations. Finally, we found that after adult MD, MBP increased in the non-deprived V1 hemisphere, but it decreased in the deprived hemisphere, and those changes were not influenced by fluoxetine. Together, the findings suggest that modulation of myelin expression in adult V1 may reflect the levels of visually driven activity rather than synaptic plasticity caused by adult plasticity.